2021
DOI: 10.1088/1361-6595/ac325e
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic plasma analysis from 1D-radial kinetic results of a Hall thruster discharge

Abstract: A radial particle-in-cell model of the weakly-collisional plasma discharge in a Hall thruster, provides the non-Maxwellian velocity distribution functions (VDF) of ions and electrons. The model considers a radial magnetic field, secondary electron emission from the two walls, and phenomenological models of anomalous electron scattering. The electron VDF is used to assess the different terms in the macroscopic momentum and energy equations, identifying those differing from the standard fluid model for a near-Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 51 publications
(127 reference statements)
4
37
0
Order By: Relevance
“…where the fitting coefficient k is set to 0.2 by matching the results of experimental measurements obtained using Xe as a propellant [24]. The anomalous collision output velocity is computed as for an elastic isotropic one, although a recent study demonstrated how the isotropic and anisotropic characters of anomalous scattering can lead to different discharge characteristics [25].…”
Section: Pic Plasma Modulementioning
confidence: 99%
“…where the fitting coefficient k is set to 0.2 by matching the results of experimental measurements obtained using Xe as a propellant [24]. The anomalous collision output velocity is computed as for an elastic isotropic one, although a recent study demonstrated how the isotropic and anisotropic characters of anomalous scattering can lead to different discharge characteristics [25].…”
Section: Pic Plasma Modulementioning
confidence: 99%
“…A 1D radial (1Dr) fully kinetic model of the radial plasma response in a cross-section of an annular HET with a radial magnetic field and dielectric walls has been developed in [53][54][55][56]. Ions and electrons are treated as PIC macroparticles while (very-slow) neutrals constitute just a background population, with the neutral density adjusted to maintain a stationary discharge.…”
Section: D-radial Kinetic Model For Hetsmentioning
confidence: 99%
“…4 1D radial results for a cross-section of a HET, based on the kinetic model of Ref. [56]. a Normalized electron VDF along v z and v r at mid channel M:…”
Section: D-radial Kinetic Model For Hetsmentioning
confidence: 99%
See 2 more Smart Citations